Analisis Faktor-Faktor Preferensi Konsumen Dalam Memilih Produk Kopi Olahan Lokal Di Kota Makassar - Mahendra, Anugerah Dwi; Azuz, Faidah; Sheyoputri, Aylee Christine Alamsyah (PALLANGGA: Journal of Agriculture Science and Research, 2024)
Coffee is one of the commodities produced from the plantation subsector which is included in the agricultural sector, which makes a large contribution to the Indonesian economy, especially as a source of foreign exchange for the country.  This research aims to identify and analyze consumer preference factors in deciding locally processed coffee products in Makassar City. This research is located in Makassar City, South Sulawesi. The population in this study were 120 consumers from three coffee shops in Makassar City. The subjects in this study were consumers of Ngumpul Coffee, Ransum Café and Hub Coffee in Makassar City. The samples for each were 15 consumers who were respondents to the three coffee shops. The research data consists of primary data and secondary data. The results of this study concluded that the consumer preference factors were: (1) Consumer preference factors based on coffee quality in terms of coffee taste, the average respondent rated it as good quality, (2) The consumer preference factor based on the average coffee price of respondents assesses the good or affordable price category, (3) The consumer preference factor is based on the availability of coffee, the average respondent assesses the available coffee category, (4) Consumer preference factors based on the menu in terms of coffee menu variants, the average respondent considers it quite interesting, and (5) The consumer preference factor based on the atmosphere in terms of the convenience of the location to enjoy coffee, the average respondent assesses the comfortable atmosphere. Kopi merupakan salah satu komoditi yang dihasilkan dari subsektor perkebunan yang termasuk dalam sektor pertanian memberikan kontribusi yang besar terhadap perekonomian Indonesia khususnya sebagai sumber devisa negara. Penelitian ini bertujuan untuk untuk mengidentifikasi dan menganalisis faktor-faktor preferensi konsumen dalam memilih produk kopi olahan lokal di Kota Makassar. Penelitian ini berlokasi di Kota Makassar, Sulawesi Selatan. Populasi dalam penelitian ini sebanyak 120 konsumen dari tiga Coffee Shop di Kota Makassar dengan subjek dalam penelitian ini yaitu konsumen Kopi Ngumpul, Ransum Café, dan Kopi Hub di Kota Makassar. Adapun sampel masing-masing sebanyak 15 konsumen yang menjadi responden pada tiga Kedai Kopi (Coffee Shop). Data penelitian ini terdiri dari data primer dan data sekunder. Hasil penelitian ini menyimpulkan bahwa faktor-faktor preferensi konsumen adalah: (1) Faktor preferensi konsumen berdasarkan kualitas kopi dari segi cita rasa kopi rata-rata responden menilai dengan kategori berkualitas baik, (2) Faktor preferensi konsumen berdasarkan harga kopi rata-rata responden menilai dengan kategori cukup atau cukup terjangkau, (3) Faktor preferensi konsumen berdasarkan ketersediaan kopi rata-rata responden menilai dengan kategori cukup atau mudah didapatkan, (4) Faktor preferensi konsumen berdasarkan menu dari segi varian menu kopi rata-rata responden menilai kurang, dan (5) Faktor preferensi konsumen berdasarkan suasana dari segi kenyamanan lokasi menikmati kopi rata-rata responden menilai baik atau sangat nyaman.